MicroRNA-506 as a tumor suppressor in anaplastic thyroid carcinoma by regulation of WNT and NOTCH signaling pathways - Zahra Nasrpour Navaei; Negin Taghehchian; Amir Sadra Zangouei; Mohammad reza Abbaszadegan; Meysam Moghbeli (Iranian Journal of Basic Medical Sciences, 2023)
Objective(s): Anaplastic thyroid carcinoma (ATC) is an aggressive thyroid tumor type that has a poor prognosis due to its high therapeutic resistance. Since ATC accounts for half of thyroid cancer-related deaths, it is required to introduce novel therapeutic targets to increase survival in ATC patients. WNT and NOTCH signaling pathways are the pivotal regulators of cell proliferation and migration that can be regulated by microRNAs. We assessed the role of miR-506 in the regulation of cell migration, apoptosis, and drug resistance via NOTCH and WNT pathways in ATC cells.Materials and Methods: The levels of miR-506 expressions were assessed in ATC cells and tissues. The levels of NOTCH, WNT, and EMT-related gene expressions were also assessed in miR-506 ectopic expressed cells compared with controls. Cell migration and drug resistance were also evaluated to assess the role of miR-506 in the regulation of ATC aggressiveness. Results: There were significant miR-506 down-regulations in ATC cells and clinical samples compared with normal cells and margins. MiR-506 suppressed NOTCH and WNT signaling pathways through LEF1, DVL, FZD1, HEY2, HES5, and HEY2 down-regulations, and APC and GSK3b up-regulations. MiR-506 significantly inhibited ATC cell migration and EMT (P=0.028). Moreover, miR-506 significantly increased Cisplatin (P=0.004), Paclitaxel (P<0.0001), and Doxorubicin (P=0.0014) sensitivities in ATC cells. Conclusion: MiR-506 regulated EMT, cell migration, and chemoresistance through regulation of WNT and NOTCH signaling pathways in ATC cells. Therefore, after confirmation with animal studies, it can be introduced as an efficient novel therapeutic factor for ATC tumors.